2021
DOI: 10.1002/14651858.cd013385.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Decision coaching for people making healthcare decisions

Abstract: BackgroundDecision coaching is non-directive support delivered by a healthcare provider to help patients prepare to actively participate in making a health decision. 'Healthcare providers' are considered to be all people who are engaged in actions whose primary intent is to protect and improve health (e.g. nurses, doctors, pharmacists, social workers, health support workers such as peer health workers).Little is known about the e ectiveness of decision coaching. ObjectivesTo determine the e ects of decision co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 308 publications
0
37
0
2
Order By: Relevance
“…A realist review methodology fits with the study purpose because it helps to uncover the mechanisms through which decision coaching works, the contextual factors that activate the mechanisms, and subsequent outcomes. This realist review was built on a Cochrane systematic review which assessed the effects of decision coaching in people facing healthcare decisions [ 1 , 2 ]. The review findings were presented based on the Realist and Meta-Review Evidence Synthesis reporting guideline [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A realist review methodology fits with the study purpose because it helps to uncover the mechanisms through which decision coaching works, the contextual factors that activate the mechanisms, and subsequent outcomes. This realist review was built on a Cochrane systematic review which assessed the effects of decision coaching in people facing healthcare decisions [ 1 , 2 ]. The review findings were presented based on the Realist and Meta-Review Evidence Synthesis reporting guideline [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The project executive group drafted an initial program theory that explained how decision coaching was thought to work and to generate the outcomes of interest from three sources: theories reported in the 28 included studies of the Cochrane systematic review [ 2 ]; theories identified in two reviews of decision coaching theories [ 3 , 14 ]; and theories provided by the executive and stakeholder group members. We screened those theories based on the criterion: whether the theory provided an explanatory focus to help uncover the mechanism(s) of how decision coaching works, rather than a descriptive account of the decision coaching process.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 36 , 38 During the SDM process, decision aids or coaching can be used to improve decision quality by addressing unresolved decisional needs. 39 , 40 To prepare the way for these SDM tools and custom design them to this population, a detailed portrait of their most difficult decisions and the variables that affect them is needed. However, no decisional needs assessment has yet been published regarding older adults or those receiving home care services specifically.…”
Section: Introductionmentioning
confidence: 99%